Pssc : physics - Schaim, Uri B.; Dodge, John H.; Walter, James A. (Lexington, Massachusetts Toronto. D.C Health and Company., 1981)
"PSSC Physics has been serving students in the United States and abroad for twenty years. The basic laws of physics have not changed during that period, but the frontiers of research, as well as new needs of technology and society, have to be reflected in secondary school physics. It would be counterproductive to try to include all the latest topics from quarks to black holes, thereby overloading the course and reducing it from a vehicle for studying nature to an aid to memorizing vocabulary."
includes appendix.
English text.
Keywords: Physics